Programa educativo de picwriting para mejorar la producción de textos escritos en inglés en estudiantes de tercer grado de secundaria en la institución educativa Maynas del distrito de Iquitos 2023 - Paredes Flores, Julissa Elizabeth (2024)
The main objective of this research work was to evaluate the effect of the Picwriting educational program on improving the production of written texts in English among third grade secondary students in the educational institution Maynas in the district of Iquitos in 2023. The type of research was evaluative with field designs, contemporary transectional, univariate and quasi-experimental, which included the administration of a pre-test, a post-test and the formation of a control group. The population consisted of 326 students, with a sample of 60 participants divided into two groups: an experimental group of 30 students and the control group of 30 students. The results at the end of the application of the program show that the average marks of the variable text production of the experimental group is higher than the average of the control group (14.464 > 9.208), likewise in its dimensions: adequacy of the text to the communicative situation (16.481> 10.815), organization and development of the text in a coherent and cohesive way (13.917> 8.389), use of conventions of written language in a pertinent way (13.605> 8.864). In conclusion, the application of the Picwriting educational program significantly improves the production of written texts in third grade high school students of the study population. with a statistical significance of p-value 0.001< α = 0.05, accepting the alternate hypothesis of study.